2021
DOI: 10.1016/j.bbih.2021.100291
|View full text |Cite
|
Sign up to set email alerts
|

Role of TRPM8 in switching between fever and hypothermia in adult mice during endotoxin-induced inflammation

Abstract: Transient receptor potential melastatin 8 (TRPM8) functions in the sensing of noxious and innocuous colds; however, its significance in pathogen-induced thermoregulation remains unclear. In the present study, we investigated the role of TRPM8 in the regulation of endotoxin-induced body temperature control. The peripheral administration of low-dose lipopolysaccharide (LPS) at 50 ​μg/kg generated fever in wild-type (WT) mice, whereas it caused hypothermia in TRPM8 knockout (KO) animals. LPS-induced sickness resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…Although mice are physiologically different from humans, it is still a widely used model. In mice, hypothermia can be displayed, but also temperature rise upon infections, particularly after LPS administrated in low doses and endotoxin [ 53 , 54 ]. Eskilsson et al (2021) have recently reported that, in mice, the humoral response is implicated in eliciting fever responses during localized inflammation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although mice are physiologically different from humans, it is still a widely used model. In mice, hypothermia can be displayed, but also temperature rise upon infections, particularly after LPS administrated in low doses and endotoxin [ 53 , 54 ]. Eskilsson et al (2021) have recently reported that, in mice, the humoral response is implicated in eliciting fever responses during localized inflammation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological methods have also been reported to either increase (adrenergic and cholinergic agonists, TRPV1 agonists, prostaglandins, catecholamines, cannabinoid, and thyroid hormone) or decrease BT (adrenergic or cholinergic antagonists, TRPA1 agonists, non-steroidal anti-inflammatory drugs, barbiturates, benzodiazepines, and opioids). Pyrogenic endotoxins such as LPS can cause hypothermia or fever, depending on their dose of administration and on ambient temperature 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…There is no apparent difference in the activation of NF-κB and STAT3 between astrocytes and tanycytes after peripheral administration of LPS ( Nakano et al, 2015 ; Muneoka et al, 2019 ). In TRM8 KO mice, ( Shiraki et al, 2021 ; Kasuga et al, 2022 ) i.c.v. injection of an LPS antagonist LPS-RS attenuates NF-κB signaling in the astrocytes and tanycytes of the CVOs after peripheral administration of LPS ( Muneoka et al, 2019 ).…”
Section: General Introductionmentioning
confidence: 99%